POTENSI PEMANFAATAN LIMBAH DAGING BUAH SEMU JAMBU METE (Anacardium occidentale) SEBAGAI SELAI - Slamet Mardiyanto Rahayu; Luis Da Costa (Nusantara Hasana Journal, 2025)
Cashew pseudo-fruit jam is a food product made from the flesh of the cashew pseudo-fruit processed into jam. Cashew, also known as monkey apple, is a fruit with a unique shape and a sweet, slightly astringent taste. Cashew pseudo-fruit jam can be a potential alternative cashew fruit processing to increase the fruit's economic value, especially in areas where many people cultivate cashew.